Morbidity following thyroid and parathyroid surgery: Results from key performance indicator assessment at a high‐volume centre in New Zealand. Issue 9 (17th August 2021) - Lin, Jin Xin; Wen, Daniel; Sharma, Avinash; van der Werf, Bert; Martin, Richard C.W.; Harman, Richard
Abstract: Background: Complications following thyroid/parathyroid surgery include recurrent laryngeal nerve (RLN) injury, hypocalcaemia and return to theatre for haematoma evacuation. Rates of these form the basis of key performance indicators (KPI). An endocrine database, containing results from 1997, was established at the North Shore Hospital in Auckland, New Zealand. We aimed to measure complication rates by procedure (thyroid and parathyroid), explore a temporal change in our unit and compare our results against international literature. Methods: A retrospective review of the database between July 1997 and February 2020 was performed. The results for each KPI were analysed in total and over consecutive time periods. A review of the literature was carried out to find international complication rates for comparison. A cumulative sum (CUSUM) analysis was performed to give visual feedback on performance. Results: There were 1062 thyroidectomies and 336 parathyroidectomies from July 1997 to February 2020. Thyroid surgery results found rates of temporary/permanent RLN injury of 1.9%/0.3%, temporary/permanent hypocalcaemia of 22.3/2.5%, and return to theatre for haematoma evacuation of 1.1%. Parathyroid surgery results were, temporary RLN injury of 0.8% (no permanent injury), temporary/permanent hypocalcaemia of 1.7%/0.4%, and return to theatre for haematoma evacuation of 0.3%. CUSUM analysis found KPI results to be comparable with international literature. Conclusion: Our unit's KPI results are comparable to published results in the literature. The use of this clinical database will help in future monitoring of performance and help drive improvement in the service. Embedding prospective data collection as routine practice allows for continuous improvement for the unit. Abstract : We review and report the results from our head and neck database at North Shore Hospital in Auckland. Our results show comparable results for key performance indicators for thyroid and parathyroid surgery.